Alterations in cardiac output in fetuses with congenital heart disease. (5th July 2022) - Sethi, Neeta; Gai, Jiaxiang; Bost, James; Donofrio, Mary T.
Abstract: Objective: Fetuses with severe congenital heart disease (CHD) have altered blood flow patterns. Prior work to assess fetal combined cardiac output (CCO) is limited by sample size and lack of longitudinal gestational data. Our aim was to evaluate CCO in CHD fetuses to determine whether the presence of single ventricle (SV) physiology or aortic obstruction impacts fetal blood flow and cardiovascular hemodynamics. Method: Prospective study including singleton fetuses with CHD ( n  = 141) and controls ( n  = 118) who underwent a mid‐ and late‐gestation fetal echocardiogram. Ventricular cardiac output was calculated using the standard computation. Combined cardiac output was derived as the sum of the right and left cardiac outputs and indexed to estimated fetal weight. Results: Fetuses with two ventricle (2V) CHD had significantly higher CCO compared to controls and SV CHD fetuses. Fetuses with SV‐CHD had similar CCO compared to controls. Fetuses with 2V‐CHD and aortic obstruction had significantly higher CCO than fetuses with SV‐CHD and aortic obstruction. Conclusion: Our findings suggest that the SV can compensate and increase CCO despite the lack of a second functioning ventricle, however, the degree of compensation may be insufficient to support the increased blood flow needed to overcome the hemodynamic and physiologic alternations seen with severe CHD. Key points: What is already known about this topic? It is thought that fetal circulatory pathways allow preservation of combined cardiac output (CCO) through shunting of blood to support intrauterine metabolic demands. Preliminary studies, however, have demonstrated lower CCO in single‐ventricle (single ventricle (SV)) heart disease (congenital heart disease (CHD)), likely secondary to disrupted blood flow patterns and/or abnormal myocardial properties. This suggests that fetuses with significant CHD may be hemodynamically affected with compromised oxygen and substrate delivery to support intrauterine metabolic needs. What does this study add? We found that fetuses with two ventricle CHD have higher CCO than controls or fetuses with SV CHD. The limited capacity of the SV to increase CCO may insufficiently compensate for systemic hypoxemia and reduced cerebral oxygen/substrate delivery in the presence of CHD. This might explain delays in cerebral structural and functional development in recent reports of neuroimaging in fetuses with significant CHD, contributing to long‐term neurodevelopmental impairments in CHD survivors.